1983
DOI: 10.1002/ana.410130204
|View full text |Cite
|
Sign up to set email alerts
|

Muscle wasting in muscular dystrophy: Decreased protein synthesis or increased degradation?

Abstract: The cause of the muscular dystrophies remains unknown. Recent publications summarize current thoughts on pathogenesis 162, 631. Because of their relatively high incidence and severity, Duchenne dystrophy and myotonic dystrophy have received the greatest attention. Although the primary defect:; in these disorders are obscure, a feature common to all muscular dystrophies is loss of skeletal muscle, which must arise because of an imbalance between muscle protein synthesis and degradation. The mechanisms of muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…In the early stages of the disease, accelerated regeneration of muscle allows for near-normal function. It is felt that it is the steady loss of regenerative capacity that results in the longterm decline in these patients (18,41,42). Consistent with this, Haslett et al (21) and Chen et al (9) compared global transcript levels from DMD muscle with those from normal muscle and found an overall upregulation of genes associated with muscle regeneration.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…In the early stages of the disease, accelerated regeneration of muscle allows for near-normal function. It is felt that it is the steady loss of regenerative capacity that results in the longterm decline in these patients (18,41,42). Consistent with this, Haslett et al (21) and Chen et al (9) compared global transcript levels from DMD muscle with those from normal muscle and found an overall upregulation of genes associated with muscle regeneration.…”
Section: Discussionmentioning
confidence: 85%
“…The most striking manifestations of this disorder are loss of skeletal muscle mass and strength, resulting in severe disability. Previous studies in DMD have suggested that the loss of muscle is likely the result of an imbalance between muscle protein synthesis and degradation (18,42). In DMD, dystrophin deficiency is present in muscle from fetal life onward.…”
mentioning
confidence: 99%
See 3 more Smart Citations